RI 9389 - Rayleigh Wave Assessment of Damage and Integrity of Mine Structures - Michael J. Friedel (The National Institute for Occupational Safety and Health (NIOSH), 2010)
The integrity of mine structures, such as the roofs, ribs, face and supporting pillars, is difficult to assess beyond the exposed surface. To mitigate potential rockfall hazards, the U.S. Bureau of Mines is assessing the usefulness of Rayleigh wave dispersion analysis to detect damage and stress-relieved zones in mine structures. Classical surface wave dispersion modeling is utilized at both laboratory and field scales in damaged and undamaged material to assess the integrity of a mine pillar and roof. To more fully exploit Rayleigh wave propagation characteristics, derivation of a novel dispersion parameter was conducted using a convolutional model. The development of a suitable Rayleigh wave dispersion system based on insight derived from forward modeling is presented. The application of inverse modeling for damage and stress assessment in the mine environment is also discussed.